Da língua portuguesa escrita à libras: problematizando processos de tradução de provas de vestibular - Reichert, Andre Ribeiro (Universidade do Vale do Rio dos Sinos, 2015)
This thesis analyzes translations from Portuguese into the Libras college entrance tests at the Federal University of Santa Maria (UFSM) in the edition of 2012. Through this analysis, we intend to answer the question: how translations of Portuguese written for Libras in college entrance test are carried out with the purpose of guaranteeing to the deaf by means of Libras, access to necessary and sufficient information regarding the knowledge required in that race? The main objective of the study is therefore to analyze elements in the process of translation, show aspects that need to take the deaf culture as central to the texts in Libras allow the deaf to understanding the issues originally presented in Portuguese writing. The conceptual considerations deal with the Translation Studies (Vasconcellos and PAGANO, 2004; Vasconcellos, 2008; Vasconcellos and BARTHOLAMEI, 2008), more specifically in the field of Libras Translation Studies and Portuguese Language (Vasconcellos, 2010; Vasconcellos, TABLES, SANTOS and PEREIRA, 2012; SANTOS, 2013). This bias comes up the socio-anthropological view of deafness (Skliar, 1998), the work of translators involved in the making of translations, specific aspects of the translation itself, as well as visual issues involved in offering the evidence (TABLES, STUMPF and OLIVEIRA, 2011; TABLES, and SOUSA VARGAS, 2012). These aspects are checked at work of translation test issues of Portuguese Language and Writing of that edition of the vestibular, in 2012. We present the proof of questions, a description of the work of translators and some implications of this process, considering the fact that deaf people have access to test information in Libras, but the answers should be given through the Portuguese language writing. As a result of the analysis, including discussions relating to impasses in the selection of strategies and settings arising from the translation process, there is the college entrance exams are a privileged locus for checking the accessibility of quality offered to deaf people, as expose the cultural and linguistic conflicts that still require research and improvements.
Keywords: Libras; Língua portuguesa escrita; Vestibular; Surdez; Oralidade; Portuguese writing; Entrance exam; Deafness; Orality; ACCNPQ::Lingüística, Letras e Artes::Lingüística